Seasonal evolution of temperatures in Titan's lower stratosphere - Sylvestre, M; Teanby, N; Vatant D'Ollone, J; Vinatier, S; Bézard, B; Lebonnois, S; Irwin, P (Elsevier, 2019)
The Cassini mission offered us the opportunity to monitor the seasonal evolution of Titan's atmosphere from 2004 to 2017, i.e. half a Titan year. The lower part of the stratosphere (pressures greater than 10 mbar) is a region of particular interest as there are few available temperature measurements, and because its thermal response to the seasonal and meridional insolation variations undergone by Titan remain poorly known. In this study, we measure temperatures in Titan's lower stratosphere between 6 mbar and 25 mbar using Cassini/CIRS spectra covering the whole duration of the mission (from 2004 to 2017) and the whole latitude range. We can thus characterize the meridional distribution of temperatures in Titan's lower stratosphere, and how it evolves from northern winter (2004) to summer solstice (2017). Our measurements show that Titan's lower stratosphere undergoes significant seasonal changes, especially at the South pole, where temperature decreases by 19 K at 15 mbar in 4 years.